Increasing proportions of extended-spectrum β-lactamase-producing isolates among Escherichia coli from urine and bloodstream infections: results from a nationwide surveillance network, Finland, 2008 to 2019 - Ilmavirta Heikki; Ollgren Jukka; Räisänen Kati; Kinnunen Tuure; Hakanen Antti J; Jalava Jari; Lyytikäinen Outi (European Centre for Disease Prevention and Control, 2025)
Background
Escherichia coli is the leading cause of urinary tract infections (UTI) and bloodstream infections (BSI), and the emergence of antimicrobial resistance (AMR) in E. coli causes concern.
Aim
To investigate changes in the proportion of extended-spectrum β-lactamase (ESBL) producing isolates among E. coli isolated from urine and blood in Finland during 2008-2019.
Methods
Susceptibility testing of 1,568,488 urine (90% female, 10% male) and 47,927 blood E. coli isolates (61% female, 39% male) from all Finnish clinical microbiology laboratories during 2008-2019 was performed according to guidelines from the Clinical and Laboratory Standard Institute during 2008-2010 and the European Committee on Antimicrobial Susceptibility Testing during 2011-2019. A binomial regression model with log link compared observed trends over time and by age group and sex.
Results
The annual proportion of ESBL-producing E. coli isolates among E. coli from blood cultures increased from 2.4% (23/966) to 8.6% (190/2,197) among males (average annual increase 7.7%; 95% CI: 4.4-11.0%, p < 0.01) and from 1.6% (28/1,806) to 6.4% (207/3,218) among females (9.3%; 95% CI: 4.8-14.0%, p < 0.01). In urine cultures, the proportion of ESBL-producing E. coli isolates increased from 2.2% (239/10,806) to 7.2% (1,098/15,297) among males (8.8%; 95% CI: 6.5-11.3%, p < 0.01) and from 1.0% (1,045/108,390) to 3.1% (3,717/120,671) among females (8.6%; 95% CI: 6.3-11.0%, p < 0.01). A significant increase was observed within most age groups.
Conclusions
Considering the ageing population and their risk of E. coli BSI and UTI, the increase in the annual proportions of ESBL-producing E. coli is concerning, and these increasing trends should be carefully monitored.
Keywords: AMR; Bacteraemia; Bloodstream infection; Drug Resistance Bacterial; ESBL; Escherichia coli; Female; Fluoroquinolone; Male; Urinary tract infection.